Distributive justice and CEO compensation - Guillermina Jasso; Eva M. Meyersson Milgrom (Institute for the Study of Labor (IZA), 2007)
This paper develops a framework for studying individuals' ideas about what constitutes just compensation for chief executive officers (CEOs) and reports estimates of just CEO pay and the principles guiding ideas of justice. The sample consists of students pursuing a Master of Business Administration (MBA) degree in Sweden and the United States. The framework, based on justice theory and making use of Rossi's factorial survey method, enables assessment of ideas of fairness in CEO compensation, including (1) the just CEO compensation, in the eyes of each observer; (2) the principles of microjustice observers' ideas about who should get what based on characteristics of CEOs and their firms; and (3) principles of macrojustice ideas about the just level and dispersion in compensation across all CEOs. Our estimates yield the following main results: First, there is broad agreement on the median just CEO compensation but substantial inter-individual variation in the principles of microjustice and the other principles of macrojustice. Second, there is remarkable similarity in the distributions of the principles of microjustice and macrojustice across the MBA groups. Other important results include a pervasive gender attentiveness among MBA students and tolerance for large variability in CEO pay.
Keywords: D31; 650; Justice theory; fairness; CEO compensation; factorial survey method; MBA students; gender; inequality; Gini coefficient; Atkinson measure; Theil's inequality measures; Führungskräfte; Gehalt; Verteilungsgerechtigkeit; Soziale Gerechtigkeit; Studierende; Meinung; Schweden; USA